Heat stress and physical capacity: a case study of semi-professional footballers. - Farideh Golbabaei; Seyyed Abolfazl Zakerian; Behzad Fouladi Dehaghi; Leila Ibrahimi Ghavamabadi; Framarz Gharagozlou; Mostafa Mirzaei Aliabadi; Rasol Hematjo (Tehran University of Medical Sciences, 2014)
The aim of this study was to determine heat stress effect on physical capacity of semi-professional footballers in Iran by means of oxygen consumption measurement, heart rate monitoring and WBGT assessment environmental conditions.This study compared two different thermal environmental conditions related to sub-maximal exercise and its effect on human physical capacity. Thirty two male footballers (age 25.9 ± 1.4 year; height 176 ± 2.9 cm and weight 71 ± 9.8 kg) were investigated under four workloads (50,100,150 & 200 W) in two different thermal conditions in the morning (WBGT=21 °C) and afternoon (WBGT=33 °C) in summer. Each test cycle lasted for 10 minutes with a 10 min interval for recovery and rest between every workload. In the end of each stage, the heart rate, blood pressure, skin temperature and oral temperature were measured and recorded. Expired air was collected and its volume was measured using standard Douglas bags. The WBGT index was also used to monitor the stressful heat condition.Heart rate and VO2 consumption findings for different workload showed a significant difference between morning and afternoon (P35 °C or WBGT>28 °C, physical activates and performing exercises should be avoided in order to reduce the risk of heat stress-related conditions in athletes.